Research of Automobile Transmission Shaft based on Finite Element Method - Zhong Zifeng; Nie Peng; Lu Jian (Jixie chuandong)
In order to improve the reliability and rationality of a automobile transmission shaft design,the free modal,torsional stiffness,static strength and fatigue strength of a transmission shaft are analyzed based on the finite element method. The result shows that the first-order natural frequency is 15% higher than the excitation frequency,so the resonance will be effectively avoided. The torsional rigidity is 27 685. 5 N·m / rad,it meets the stiffness requirement. The maximum stress is located at the shaft tube,its value is 185. 2 MPa,the safety factor is 1. 32,it meets the strength requirements. The minimum life is 8. 165 × 107,it meets the fatigue life requirements.